2022
DOI: 10.1002/viw.20200181
|View full text |Cite
|
Sign up to set email alerts
|

Detection, prevention and treatment of COVID‐19 and opportunities for nanobiotechnology

Abstract: Since the outbreak of COVID‐19, the number of confirmed cases and deaths has increased globally at a dramatic speed. In view of the serious health threat to humans, this review discusses the state‐of‐the‐art studies about fighting this disease. It summarizes the current strategies and recent advances in detecting, preventing, and treating COVID‐19 and interprets the underlying mechanisms in detail. Detection of COVID‐19 can be successfully achieved by multiple techniques such as polymerase chain reaction, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 133 publications
(269 reference statements)
0
6
0
Order By: Relevance
“…The limit of detection (LOD) with PdAu@Au CNCs was measured to be 10-50 µmol L −1 (Figure S11, Supporting Information), which is almost a tenth of the physiological concentration in bio-fluids (200-500 µmol L −1 ). [17] These results concluded that the PdAu@Au CNCs can induce notable signal enhancement in both SERS and LDI-MS detection compared to the monomeric counterparts.…”
Section: Designed Alloy Substrate Materials For Sers/ldi-ms Co-detectionmentioning
confidence: 84%
“…The limit of detection (LOD) with PdAu@Au CNCs was measured to be 10-50 µmol L −1 (Figure S11, Supporting Information), which is almost a tenth of the physiological concentration in bio-fluids (200-500 µmol L −1 ). [17] These results concluded that the PdAu@Au CNCs can induce notable signal enhancement in both SERS and LDI-MS detection compared to the monomeric counterparts.…”
Section: Designed Alloy Substrate Materials For Sers/ldi-ms Co-detectionmentioning
confidence: 84%
“…In this regard, NPs can be used as antiviral drug to treat various viral infections. The use of NPs provides an opportunity for the development of new antiviral therapies, and the possibility of drug resistance is very low compared with traditional chemical antiviral therapies (Bao et al, 2022; Gurunathan et al, 2020). These characteristics make them interesting candidate materials for therapeutic drugs or surface coatings to neutralize viruses (N. Lin et al, 2021).…”
Section: Application Of Zno Nmts To Viruses and Their Mechanisms Of A...mentioning
confidence: 99%
“…PCR is the gold standard for clinical COVID-19 diagnosis but suffers from a high false-negative rate (9.3-16.7%) and time-consuming procedures (approximately hours), [38] which makes it essential to develop more accurate and faster diagnostic techniques for epidemic prevention purpose. [39] LDI MS based molecular approaches have been approved as a potential solution for COVID-19 diagnostics according to previous literature (accuracy of 90-99%), [9c,40] owing to the balance between analytical throughput, speed, and result performance. However, LDI MS based downstream metabolites analysis for COVID-19 diagnosis and metabolic-biomarker selection has not been reported yet.…”
Section: Sars-cov-2 Diagnosis and Metabolic-biomarker Panel Discoverymentioning
confidence: 99%